(untitled) (REMUNOM, 2025)
This article investigates the tax system of the municipality of Linhares, in Espírito Santo, with a focus on property taxes: the Urban Predial and Territorial Tax (IPTU) and the Transfer of Real Estate Tax (ITBI). Their origins, the current legislation, the main obstacles faced by the municipality in the collection of these taxes and reform proposals to improve their application are explored. Additionally, the study conducts a comparative analysis of the IPTU of Linhares with the municipalities of Vitória and Cachoeiro de Itapemirim, regarding the quotas and payment conditions. The methodology employed is based on bibliographic review and analysis of available public data, seeking to base the proposals on theoretical and empirical foundations. Through this approach, a more fair, efficient and transparent municipal tax model is proposed, contributing to fiscal sustainability and local development. The text also highlights the importance of timely payment of taxes as a way of ensuring the continuity of public services and the quality of urban infrastructure.